Spectrum and functional validation of PSMB5 mutations in multiple myeloma - Barrio, Santiago; Giesen, Nicola; Raab, Marc-Steffen (Leukemia, 2019)
Despite an increasing number of approved therapies, multiple myeloma (MM) remains an incurable disease and only a small number of patients achieve prolonged disease control. Some genes have been linked with response to commonly used anti-MM compounds, including immunomodulators (IMiDs) and proteasome inhibitors (PIs). In this manuscript, we demonstrate an increased incidence of acquired proteasomal subunit mutations in relapsed MM compared to newly diagnosed disease, underpinning a potential role of point mutations in the clonal evolution of MM. Furthermore, we are first to present and functionally characterize four somatic PSMB5 mutations from primary MM cells identified in a patient under prolonged proteasome inhibition, with three of them affecting the PI-binding pocket S1. We confirm resistance induction through missense mutations not only to Bortezomib, but also, in variable extent, to the next-generation PIs Carfilzomib and Ixazomib. In addition, a negative impact on the proteasome activity is assessed, providing a potential explanation for later therapy-induced eradication of the affected tumor subclones in this patient.
Published online: 19 July 2018
Gesehen am 19.11.2019